DNA polymerases beta and lambda mediate overlapping and independent roles in base excision repair in mouse embryonic fibroblasts. - Elena K Braithwaite (Public Library of Science (PLoS), 2010)
Base excision repair (BER) is a DNA repair pathway designed to correct small base lesions in genomic DNA. While DNA polymerase beta (pol beta) is known to be the main polymerase in the BER pathway, various studies have implicated other DNA polymerases in back-up roles. One such polymerase, DNA polymerase lambda (pol lambda), was shown to be important in BER of oxidative DNA damage. To further explore roles of the X-family DNA polymerases lambda and beta in BER, we prepared a mouse embryonic fibroblast cell line with deletions in the genes for both pol beta and pol lambda. Neutral red viability assays demonstrated that pol lambda and pol beta double null cells were hypersensitive to alkylating and oxidizing DNA damaging agents. In vitro BER assays revealed a modest contribution of pol lambda to single-nucleotide BER of base lesions. Additionally, using co-immunoprecipitation experiments with purified enzymes and whole cell extracts, we found that both pol lambda and pol beta interact with the upstream DNA glycosylases for repair of alkylated and oxidized DNA bases. Such interactions could be important in coordinating roles of these polymerases during BER.